Measuring multicultural effectiveness among self-initiated academic expatriates in Malaysia - Haslina Halim,; Hassan Abu Bakar,; Bahtiar Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Being an academic entity, universities offer a distinct environment with different missions and work tasks as compared to business organizations. Thus far only a minimal amount of investigation has embarked on self-initiated expatriates in the academic field. Therefore, the main aim of the research is to investigate the adjustment of this group of expatriates by focusing on the relationships between multicultural personality skills and the academic expatriates’ personal, professional and social adjustment by utilizing the multicultural personality scale (MPQ). The MPQ consists of five dimensions - cultural empathy, open-mindedness, social initiative, emotional stability and flexibility. Besides MPQ constructs, the study also examines the relationship between language ability and the expatriates’ personal, social and professional adjustment. One-hundred and one questionnaires were distributed to self-initiated academic expatriates (N=101) attached to various academic departments in UUM. Results revealed that open-mindedness and flexibility are significantly related to the expatriates’ personal adjustment, while cultural empathy, emotional stability and flexibility are significantly related to social adjustment. Flexibility is the only dimension of MPQ that predicts academic expatriates’ professional adjustment. Language skills on the other hand, do not show any significant relationship with all three types of adjustments. Apart from the results, the discussions and limitations of the study are also presented in the paper.